Human sex hormone-binding globulin as a potential target of alternate plasticizers: an in silico study. (September 2016) - Sheikh, Ishfaq; Yasir, Muhammad; Abu-Elmagd, Muhammad; Dar, Tanveer; Abuzenadah, Adel; Damanhouri, Ghazi; Al-Qahtani, Mohammed; Beg, Mohd
Abstract Background Currently, alternate plasticizers are used to replace phthalate plasticizers in children's toys, medical equipments and food packaging, due to the adverse effects of phthalate compounds on human health and laws prohibiting their use. Current information regarding the safety and potential adverse effects of alternate plasticizers is limited and recent studies have found alternate plasticizers to display similar characteristics to those observed in phthalate plasticizers. This study was undertaken to evaluate and predict the potential endocrine disrupting activity of the three most commonly used alternate plasticizers: di(2-ethylhexyl)terephthalate (DEHT), tris(2-ethylhexyl)trimellitate (TOTM), and diisononyl hexahydrophthalate (DINCH) against human sex hormone-binding globulin (SHBG) usingin silico approaches. Materials and methods The crystal structure of human SHBG (Id: 1D2S) was retrieved from Protein Data Bank. PubChem database was searched for the structures of alternate plasticizers, DEHT, TOTM, and DINCH. Docking was performed using Glide (Schrodinger) Induced Fit Docking module. Results Induced Fit Docking of three alternate plasticizer compounds indicated that each of the three compounds fitted well into the steroid binding pocket of SHBG. Docking displays showed interactions of alternate plasticizers with 25–30 amino-acid residues of SHBG; 18–20 amino residues overlapped between the natural ligand, DHT, and the three compounds (commonality of 82–91 %). The hydrogen-bonding interaction of the amino-acid residue, Asn-82, of SHBG was also present in displays of DHT and all the three alternate phthalates. The binding affinity of all the three alternate phthalates was higher than DHT; maximum in DINCH followed by TOTM and DEHT. Conclusion Our results suggested that the three alternate plasticizers have potential to engage the important interacting residues of SHBG and thus interfere in its steroid homeostatic function.